Literature Review : Digital Integration to Start a Sustainable Dream Business - Amelia Setyawati; Djoewita Djoewita; Amelia Sugangga; Ludi Wishnu Wardana; Agus Hermawan (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The aim of this research is to investigate the concrete steps needed to start a dream business in the era of digital transformation. Through a step-by-step approach, researchers intend to provide practical guidance for entrepreneurs who want to utilize digital technology to create sustainable businesses. The novelty of this research lies in its systematic and detailed approach in assembling the steps needed to start a dream business. By emphasizing the importance of integrating digital technology in every stage, researchers bring the concept of digital transformation from theory to practice. The urgency of this research is increasingly felt amidst changing market dynamics and pressure to adapt to technological changes. Businesses that are unable to adapt to these changes risk being left behind and losing their competitive edge. The method used in this research is Systematic Literature Review (SLR) by collecting relevant previous research through publish or publish then analyzing the article and narrowing it down regarding keywords. Through a literature review approach, the author explores the basic concepts of digital business transformation and its implementation framework in the context of a start-up business. Researchers detail the basic concepts of digital business transformation and the urgency of implementing them among business actors. The results of this research provide practical guidance that can help entrepreneurs start their dream business with targeted and effective steps. By utilizing digital technology wisely, businesses can increase their operational efficiency and expand market reach. Researchers also provide implications regarding the importance of awareness and skills in utilizing digital technology as a tool to achieve business goals. Additionally, the emphasis on business sustainability underscores the importance of considering the environmental and social impacts of business activities. As a recommendation , entrepreneurs are advised to continue to develop digital literacy and actively seek opportunities to integrate technology in their business strategies. Additionally, collaboration with other stakeholders, including governments and non-governmental organizations, can help create a business ecosystem that supports sustainability and innovation